Structure and selected properties of polyamide 6/organophilized montmorillonite nanocomposites - Szustakiewicz, K.; Steller, K.; Pigłowski, J. (Polimery, 2013)
The paper presents the results of a study on the nanocomposites prepared from polyamide 6 (PA 6) and montmorillonite, organophilized with two quaternary ammonium salts of different chemical structures (MO1, MO2), used as a filler at a concentration of 5 wt.%. The PA 6/organophilized montmorillonite composites were prepared using a co-rotating twin screw extruder. The test samples were made by injection or compression moulding. The structure of nanocomposites, in particular the degree of nanofiller exfoliation, was assessed using WAXS and TEM methods. The produced nanocomposites were characterized for the mechanical, rheological and thermal properties as well as flammability. It was found that the type of organically modifying agent exerts a substantial influence on the degree of nanofiller dispersion in a polyamide matrix, and in effect, on the final properties of nanocomposites.